2014
DOI: 10.4149/neo_2014_012
|View full text |Cite
|
Sign up to set email alerts
|

Decreased expression of Small glutamine-rich tetratricopeptide repeat-containing protein (SGT) correlated with prognosis of Hepatocellular carcinoma

Abstract: Small glutamine-rich tetratricopeptide repeat-containing protein (SGT) is an ubiquitously expressed cochaperone of heat shock cognate protein of 70 kDa (Hsc70). SGT binds to the C terminus of Hsc70 to recruit Hsc70 into complexes of diverse function. SGTB was identified as an isoform of SGT with 60% amino acid sequence homology. To investigate the expression of SGTB in hepatocellular carcinoma (HCC) and determine its correlation with tumor progression and prognosis, we evaluated the expression levels of SGTB i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…Small glutamine-rich tetratricopeptide repeat-containing protein (SGT), including SGTA and SGTB, was first identified as a protein interacting with HIV type 1 and parvovirus H-1 [23] and is an ubiquitously expressed molecular chaperone of Hsc70 [24]. SGTB was found to be dramatically decreased in HCC tissues, and low expression level of SGTB was shown to be associated with histological grade, HBsAg expression and a poor prognosis [25]. Tian et al [47] found that miR-365b functioned as a cancer-promoting gene and promoted hepatocellular carcinoma motility and spreading by suppressing SGTB expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Small glutamine-rich tetratricopeptide repeat-containing protein (SGT), including SGTA and SGTB, was first identified as a protein interacting with HIV type 1 and parvovirus H-1 [23] and is an ubiquitously expressed molecular chaperone of Hsc70 [24]. SGTB was found to be dramatically decreased in HCC tissues, and low expression level of SGTB was shown to be associated with histological grade, HBsAg expression and a poor prognosis [25]. Tian et al [47] found that miR-365b functioned as a cancer-promoting gene and promoted hepatocellular carcinoma motility and spreading by suppressing SGTB expression.…”
Section: Discussionmentioning
confidence: 99%
“…SGT has two forms: SGT alpha (SGTA) and SGT beta (SGTB) [24]. SGTB was found to be dramatically decreased in hepatocellular carcinoma (HCC) tissues compared to normal liver tissues, and downregulation of SGTB was shown to be related to histological classification, HBsAg expression and a poor prognosis [25]. Here, we found that miR-514b-5p was dramatically upregulated in NSCLC tissues, and miR-514b-5p expression was positively associated with poor outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The protein encoded by ABCG5 (fold change 16.35) is one of the ATP-binding cassette (ABC) transporters superfamily members, involved in extra and intracellular membrane transport of different molecules and, in particular, of neutral sterol in hepatobiliary and transintestinal cholesterol excretion and its inactivating mutations cause a rare genetic disorder, Sitosterolemia [44]. SGTB (fold change 3.09) encodes small glutamine-rich tetratricopeptide repeat containing beta, an isoform of SGT, a co-chaperone of heat shock cognate protein of 70 kDa (Hsc70), and its down-regulation by miR-365b enhances HCC cell migration and invasion in vitro and low SGTB tissue expression was found correlated with more favorable HCC progression and prognosis [45,46]. The protein-coding gene SER-PINH1 (fold change 2.80) encodes a member of the serine protease inhibitor superfamily.…”
Section: Loss Of Macroh2a1 Histone Variants Changes the Expression Of Circadian Genes In Hcc Cellsmentioning
confidence: 99%